Іншомовне в новій лексиці (матеріали до словника) - Тищенко, О. (Лексикографічний бюлетень, 2012)
The article analyzes the ways of certification of register units and lexicographic sources in the dictionary materials intended for identifying and fixing new words in the modern Ukrainian language. Special means are used, such as graphic characters indicating some peculiarities of recording the words in other dictionaries as well as their significance, functional use, etc. This encourages diachronic and synchronic observation of the development of lexical units in language and in lexicographic interpretation.